A quantitative evaluation of theoretical renewable energy potential of the building site - Žėkas, Vygantas; Martinaitis, Vytautas; Streckienė, Giedrė; Vilutienė, Tatjana (Journal of Civil Engineering and Management, 2014)
Modern building design process is becoming more complex. Local conditions and future constructions are computer-simulated. The aim of this simulation is to evaluate theoretical RE potential for the successful and efficient exploitation of the new building. As usual, in the simulation process of local conditions, the assessment of the renewable energy potential is one of the key elements. This article presents and analyses the idea of the quantitative evaluation of renewable energy (RE) theoretical potential of the building site and the approach on how to prepare initial data file for further process of site energy development concept creation. The study describes a building site that is undergoing the RE evaluation in terms of thermodynamic and descriptive statistics characteristics. The applicability of the offered approach was verified in the case study. The specified evaluation of the combined energy fluctuation throughout the year provides new and potentially crucial information about the issues of the RE hybrid energy transformation systems’ modelling and about the efficient use of resources to ensure the same level of energy services.